Analisis Efektivitas Pelayanan Kesehatan Pasien di Rumah Sakit Umum Daerah (RSUD) Masohi Kabupaten Maluku Tengah - Sapulette, Rezita AN; Rengifurwarin, Zainal Abidin; Bahasoan, Aminah (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the effectiveness of healthcare services at RSUD Masohi, Central Maluku Regency, using the five organizational effectiveness indicators proposed by Gibson Ivancevich Donnelly (1985), namely production, efficiency, satisfaction, adaptability, and development. A descriptive qualitative approach was applied, with data collected through in-depth interviews, direct observation, and document review. The findings indicate that in terms of production, the breakdown of critical facilities such as the CSSD hindered major surgical operations and reduced service capacity. Regarding efficiency, the manual claims administration system slowed down processes and reduced service accuracy. Patient satisfaction levels varied, with complaints about comfort, service speed, and facility completeness. The hospital’s adaptability to change remained reactive, lacking a comprehensive strategic plan, particularly in responding to facility crises and technological advancements. Development efforts were also limited, as reflected in minimal infrastructure investment, insufficient medical staff training, and restricted specialist services. These findings highlight the urgent need for a comprehensive and sustainable improvement strategy, encompassing infrastructure enhancement, adoption of health information technology, capacity building for human resources, and expansion of specialized healthcare services. Consequently, RSUD Masohi is expected to improve its service effectiveness and quality to optimally meet the healthcare needs of the community.